The Concept of “Baku Masuk” as A Symbol of The Culture of Harmony In Ambon - Tuanany, Nurlaila; Manaf Tubaka, Abdul (Balai Diklat Keagamaan Ambon, 2022)
This paper aims to describe how the dominant culture of the Ambonese can be used as a symbol of harmony in cultural plurality and ethnic pluralism in Ambon City. The cultural plurality that has been segregated through knowledge of territorial and geographical boundaries as a differentiator can be overcome through the